Analisis Kompetensi Pedagogik Guru Dan Motivasi Belajar Siswa Terhadap Hasil Belajar Siswa Kelas XII IPS Pada Mata Pelajaran Ekonomi Di SMA Negeri 2 Sukoharjo Tahun Ajaran 2016 / 2017 - Aminawati, Erla; Dr. Wafrotur Rohmah, Dr. Wafrotur Rohmah M.M (2017)
The purpose of this study are : 1) To determine the nfluence of pedagogical competence of teachers to student learning outcomes on economic subjects students of class XII IPS SMA Negeri 2 Sukoharjo the academic year 2016 / 2017. 2) To determine the influence student motivation toward student learning outcomes in economic subjects students of class XII IPS SMA Negeri 2 Sukoharjo the academic year 2016 / 2017. 3) To determine the influence of pedagogical competence of teachers and students' motivation for learning outcomes on economic subjects students of class XII IPS SMA Negeri 2 Sukoharjo. This research uses quantitative research.The population in this study were all students of class XII IPS SMA Negeri 2 Sukoharjo as many as 128 students.The sampling technique used Sample random Sampling that as many as 95 respondents. Data collecting pass documentation and enquette .This research use quantitative research type. The questionnaire has previously been tested amd tested for validity and reliability were tested. Data analysis technique used is the prerequisite analysis using normality test and linearity test, whereas hypothesis testing using multiple linear regression, F test, t-test, R2, and the relative contribution and effective.This research use quantitative research type .The results of the regression equation obtained regression equation pedagogical competence of teachers is Y = 29.241 + 0,379X1 + 0,559X2. This means that teachers Pedagogic Competence and Motivation affects Student Learning Outcomes. t test results pedagogical competence of teachers significantly influence Student Results showed tcount> ttable (2,917> 1,986) with a level of significance below 0.05 is 0.004. t test results Students' motivation significant effect on student learning outcomes showed tcount> t table (4.142> 1.986) with a level of 0.05 is signigikasi below 0,000. F test results Pedagogic Competence Teacher and Student Motivation jointly significant effect on results Student shows the F count> F table (27.448> 3.095) with a level of 0.05 is signigikasi below 0,000. Based on the calculation of Relative Contribution (SR) Padagogical Teacher (X1) of 38.80% and Motivation (X2) amounted to 61.20%. While Donations Effective (SE) for Teachers Pedagogical Competence (X1) of 14.50% and Motivation (X2) amounted to 22.87%. The test results obtained determination coefficient R2 = 0.374, meaning that 37.4% showed variable Y (Learning Outcomes) is affected by the variable X (Pedagogic Competence Teacher and Student Motivation) while the remaining 62.6% is influenced by other variables. Keywords: learning outcomes, pedagogic competence teacher, student motivation